PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN KOMPENSASI TERHADAP KEPUASAN KERJA MELALUI KINERJA KARYAWAN DI PT BANK SINARMAS Tbk. CABANG SURABAYA - Angga Harman Firmansyah (Prodi Magister Manajemen Universitas Wijaya Putra, 2017)
PT. Bank Sinarmas Tbk Surabaya Branch is one of the subsidiaries of PT. Sinarmas Bank which operates in Surabaya city area has the number of employees 128 people. In the era of banking competition is quite tight, companies can not deny the performance of employees. It is possible situational leadership style and compensation have effect on employee job satisfaction through performance appraisal indicator. The purpose of this study is to know, describe and analyze the relationship of situational leadership style, compensation, employee performance and employee job satisfaction. This research is an exsplanatory. This research uses quantitative approach, with statistical method of path analysis. The result of the research shows that leadership style has significant effect on employee job satisfaction, compensation has significant effect to job satisfaction, performance has significant effect to job satisfaction, situational leadership style influences the employee performance, compensation has significant effect on performance, situational leadership style influences the job satisfaction, compensation through employee performance has a significant effect to job satisfaction.